Nearly Synchronous Multidecadal Oscillations of Surface Air Temperature in Punta Arenas and the Atlantic Multidecadal Oscillation Index - Kayano, Mary Toshie; Setzer, Alberto W. (Journal of climate, 2018)
The Atlantic multidecadal oscillation (AMO) signature in southern South America (SA) is examined using the surface air temperature (T-air) of Punta Arenas, Chile (53.0°S, 70.85°W), during the 1888–2016 period. The T-air shows multidecadal oscillations with a significant positive correlation of 0.77 to the AMO index. The relations of the Punta Arenas T-air time series with the AMO-related global sea surface temperature (SST) and regional circulation anomaly patterns are discussed. During the warm (cold) AMO phase, a cold (warm) center in southwestern Atlantic waters induces low-level anticyclonic (cyclonic) anomalies in the region, which together with the cyclonic (anticyclonic) anomalies in the southeastern Pacific channel the northerly (southerly) flow over southern SA. This meridional flow transports warm (cold) air from lower (higher) latitudes into the Punta Arenas region. Therefore, the temperature horizontal advection at the low level is the main thermodynamic process that alters the Punta Arenas T-air in a multidecadal time scale. The use of a relation between a long T-air surface sensor series in southern SA with the AMO presents a novel approach in climate monitoring and modeling.